Design, synthesis, and evaluation of cyclic C7-bridged monocarbonyl curcumin analogs containing an o-methoxy phenyl group as potential agents against gastric cancer - Xin Gan; Yuna Wu; Min Zhu; Bo Liu; Miaomiao Kong; Zixuan Xi; Ke Li; Haibao Wang; Tiande Su; Jiali Yao; Fatehi Khushafah; Baozhu Yi; et al. (Taylor & Francis Group, 2024)
AbstractThe structure-activity relationship (SAR) between toxicity and the types of linking ketones of C7 bridged monocarbonyl curcumin analogs (MCAs) was not clear yet. In the pursuit of effective and less cytotoxic chemotherapeutics, we conducted a SAR analysis using various diketene skeletons of C7-bridged MCAs, synthesized cyclic C7-bridged MCAs containing the identified low-toxicity cyclopentanone scaffold and an o-methoxy phenyl group, and assessed their anti-gastric cancer activity and safety profile. Most compounds exhibited potent cytotoxic activities against gastric cancer cells. We developed a quantitative structure-activity relationship model (R2 > 0.82) by random Forest method, providing important information for optimizing structure. An optimized compound 2 exhibited in vitro and in vivo anti-gastric cancer activity partly through inhibiting the AKT and STAT3 pathways, and displayed a favorable in vivo safety profile. In summary, this paper provided a promising class of MCAs and a potential compound for the development of chemotherapeutic drugs.